Thermal decomposition and stability of [Fe(eta(4)-enone)(CO)(2)L] complexes (L=CO and PPh3) - Zutin, K.; Nogueira, V. M.; Mauro, A. E.; de Souza, G. R.; Klein, S. I. (Springer, 2007)
The compounds [Fe(bda)(CO)(2)L] and [Fe(ch)(CO)(2)L], (bda=benzylideneacetone; ch=chalcone; L=CO, PPh3) were investigated by thermogravimetry and derivative thermogravimetry (TG and DTG). The fragmentation patterns suggest that the iron atom protects the enone fragment, so that the organic ligands break up with the loss of the pendant aromatic rings.
Keywords: carbonyliron; enones; thermal analysis; triphenylphosphane